2005
DOI: 10.1111/j.1365-2710.2005.00659.x
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of antimicrobial prophylaxis in paediatric surgery and its financial implication

Abstract: The results showed a significantly high level of inappropriate use of antimicrobial prophylaxis in paediatric surgery in Singapore. However, when the individual factors such as appropriate choice of antibiotics, appropriate timing and duration were considered, the situation was very similar to the results obtained from overseas studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
4
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 26 publications
1
22
4
3
Order By: Relevance
“…Despite the availability of written guidelines in almost all centers, antibiotics were administered with the induction of anaesthesia in 65% of centers, which is similar to the incidence reported in other studies (13%-69%) [6,8,9,12,13]. Furthermore, the questionnaire may have over-estimated real-life adherence to the correct timing of antibiotic administration, since even hospitals where specific programs on surgical antibiotic prophylaxis have been implemented report suboptimal (92%) adherence [6].…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Despite the availability of written guidelines in almost all centers, antibiotics were administered with the induction of anaesthesia in 65% of centers, which is similar to the incidence reported in other studies (13%-69%) [6,8,9,12,13]. Furthermore, the questionnaire may have over-estimated real-life adherence to the correct timing of antibiotic administration, since even hospitals where specific programs on surgical antibiotic prophylaxis have been implemented report suboptimal (92%) adherence [6].…”
Section: Discussionsupporting
confidence: 73%
“…Many studies have been conducted on the quality of and adherence to antibiotic prophylaxis in different surgical settings [7][8][9][10][11][12][13], while data on adherence to aspects other than antibiotic prophylaxis are limited.…”
Section: Introductionmentioning
confidence: 99%
“…Some of studies show that many children may not receive antibiotics were proven benefit and could receive antibiotics when there is no clear indication for it [29]. The appropriate use of antibiotics could lead to essential saving not only for the hospital and patient but also for the health care system [30] and can help to decrease the incidence of the surgical site infection and hospital related costs. At the same time overuse of antibiotics can lead to the emergence or resistant microorganisms [13].…”
Section: Discussionmentioning
confidence: 98%
“…8,9 However, despite availability of various guidelines, [4][5]10 prior reports suggest that clinician's behavior has changed little and compliance remains suboptimal, 11,12 particularly in pediatric surgery in which the benefits of antibiotics in children and adolescents are uncertain. 13,14 In a 5-year retrospective study of general surgery and urology in 22 children's hospitals, only 82% of patients received antibiotics when prophylaxis was indicated, and 40% of patients were given antibiotics without indication. 13 A pediatric surgical study in Singapore reported that 57% of patients had appropriate antibiotics, 76% timely administration, and 41% appropriate duration, with 13% overall compliance.…”
mentioning
confidence: 99%
“…13 A pediatric surgical study in Singapore reported that 57% of patients had appropriate antibiotics, 76% timely administration, and 41% appropriate duration, with 13% overall compliance. 14 Although comparison among studies is difficult because definitions of compliance differed, few of these studies provided explicit strategies for implementation, which is essential for effective uptake of guideline recommendations. 15 Pathman et al 16,17 proposed a 4-stage model to understanding utilization of clinical practice guidelines: awareness, agreement, adoption, and adherence.…”
mentioning
confidence: 99%